An advanced hydraulic fracturing technique: Pressure propagation and attenuation mechanism of step rectangular pulse hydraulic fracturing. Issue 1 (2nd November 2022) - He, Pei; Lu, Zhaohui; Deng, Zhi; Huang, Yongkui; Qin, Dawei; Ouyang, Liming; Li, Menglai
Abstract: Hydraulic fracturing technology has played a pivotal role as a key technology in shale gas development, but the geological environmental problems caused have been worrying the public. This paper proposes an advanced step rectangular pulse hydraulic fracturing technique, which can achieve higher pressure and more complex fractures by pumping lower energy fluid. The results indicate that the pressure propagation of step rectangular pulse hydraulic fracturing can be divided into stable and unstable propagation stages. Compared with conventional hydraulic fracturing, longer unsteady propagation time, higher pressure and more complex pressure distribution can be obtained. Step pulse parameters are discussed. We found that the pulse pressure increases linearly with the increase in pulse amplitude. There are optimal pulse frequencies and comprehensive damping coefficients to get optimal fluid pressure in different shale reservoirs. These research results will help reduce geological environmental hazards, and can also provide guidance for the optimization of step rectangular pulse hydraulic fracturing technology in shale reservoirs. Abstract : The paper proposes an advanced step rectangular pulse hydraulic fracturing technique, which can achieve higher pressure and more complex fractures by pumping lower energy fluids. These research results will help reduce geological environmental hazards, and can also provide guidance for the optimization of step rectangular pulse hydraulic fracturing technology in shale reservoirs.